Enhanced photochemical catalysis of TiO2 inverse opals by modification with ZnO or Fe2O3 using ALD and the hydrothermal method. (15th February 2018) - Liu, Jiatong; Sun, Cuifeng; Fu, Ming; Long, Jie; He, Dawei; Wang, Yongsheng
Abstract: The development of porous materials exhibiting photon regulation abilities for improved photoelectrochemical catalysis performance is always one of the important goals of solar energy harvesting. In this study, methods to improve the photocatalytic activity of TiO2 inverse opals were discussed. TiO2 inverse opals were prepared by atomic layer deposition (ALD) using colloidal crystal templates. In addition, TiO2 inverse opal heterostructures were fabricated using colloidal heterocrystals by repeated vertical deposition using different colloidal spheres. The hydrothermal method and ALD were used to prepare ZnO- or Fe2 O3 -modified TiO2 inverse opals on the internal surfaces of the TiO2 porous structures. Although the photonic reflection band was not significantly varied by oxide modification, the presence of Fe2 O3 in the TiO2 inverse opals enhanced their visible absorption. The conformally modified oxides on the TiO2 inverse opals could also form energy barriers and avoid the recombination of electrons and holes. The fabrication of the TiO2 photonic crystal heterostructures and modification with ZnO or Fe2 O3 can enhance the photocatalytic activity of TiO2 inverse opals.